YouTube : illegally tracking children's data - Gordon, Zachary; Ilyas, Nasir; O'Rourke, James S., 1946- (London : The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame, 2019)
Google subsidiary, YouTube, has collected data of children users without the consent of parents and then sold the data to advertisers. The Federal Trade Commission fined Google $170 million in what was the largest fine in Google's history. Absent a plausible public explanation, YouTube and its parent company risk anger and alienation from investors, application users, parents groups, and perhaps further regulatory oversight from the Congress of the United States.
Originally Published In Gordon, Z., Ilyas, N., & O'Rourke, J. (2019). YouTube: Illegally Tracking Children's Data. 19-18. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; YouTube (Firm) -- Management; YouTube (Firm) -- Public relations; YouTube (Firm) -- Data processing; Google (Firm)